Identification of SNPs within the CYP2A6 enzyme of TNBC cell lines and the resulting change in activity - Dingle, Laura Margaret Kirkpatrick (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2017)
Expected release date-May 2019
Keywords: Uncatalogued